CFL1 and Arp3 are Biomarkers for Metastasis and Poor Prognosis of Squamous Cell/Adenosquamous Carcinomas and Adenocarcinomas of Gallbladder. (4th February 2013) - Yang, Zhu-Lin; Miao, Xiongying; Xiong, Li; Zou, Qiong; Yuan, Yuan; Li, Jinghe; Liang, Lufeng; Chen, Meigui; Chen, Senlin
<x xml:space="preserve">Abstract</x> Cofilin-1 (CFL1) and Arp3 expression in 46 squamous cell and adenosquamous carcinomas (SC/ASCs) and 80 adenocarcinomas (ACs) were measured by using immunohistochemistry. Positive CFL1 and Arp3 expression were significantly associated with large tumor size, high TNM stage, lymph node metastasis, and decreased overall survival in both SC/ASC and AC patients (p < .001). Multivariate Cox regression analysis showed that positive CFL1 and Arp3 expression are independent poor-prognostic factors for both SC/ASC and AC patients. Our study suggested that positive CFL1 and Arp3 expression are closely related to tumor progression, metastasis, and poor prognosis of gallbladder cancer.